G-Protein Beta3 Subunit C825T Polymorphism in Patients With Overlap Syndrome of Functional Dyspepsia and Irritable Bowel Syndrome - Kim, Han Gyeol; Lee, Kwang Jae; Lim, Sun Gyo; Jung, Jae Yeon; Cho, Sung Won (Journal of neurogastroenterology and motility, 2012)
Guanine nucleotide binding protein (G-protein) beta polypeptide 3 (GNB3) C825T polymorphism alters intracellular signal transduction, which may lead to motor or sensory abnormalities of the gastrointestinal tract. The aim of the present study was to evaluate the association of the GNB3 C825T polymorphism with susceptibility to overlap syndrome of functional dyspepsia (FD) and irritable bowel syndrome (IBS) in a Korean population. One hundred sixty-seven patients with FD alone, 60 patients with IBS alone, 85 patients with the overlap of FD and IBS, and 434 asymptomatic healthy subjects participated in the study. Genotyping for GNB3 C825T polymorphism was performed using their blood samples. No association of GNB3 genotypes in patients with FD alone, IBS alone or overlap phenotype, when compared to genotypes in controls, was detected. The frequency of CT and TT genotypes relative to the CC genotype for the phenotypes of FD alone, IBS alone and the coexistence of FD and IBS did not significantly differ. Comparison of the TT genotype with the CC/CT genotype showed no significant association for each phenotype group. There is no apparent association of the GNB3 C825T polymorphism with the susceptibility to FD, IBS or the overlap of FD and IBS. Larger-scale studies and further investigation on other candidate genes are required.